The Journeys of Inkarri and the Scene of Encounter: A Reading of Los juicios finales, by Peter Elmore - Muñoz-Díaz, Javier (2023)
Los juicios finales, Peter Elmore’s latest and most ambitious book of criticism, is a fundamental contribution to the study of the Peruvian cultural and intellectual field in the second half of the 20th century. Based on a meticulous bibliographical reconstruction, the book establishes that the discovery of the Inkarri mythical cycle between 1955 and 1956 originated the most widespread and influential lettered vision of Andean mentalities. The Peruvian intelligentsia postulates indigenous peasants as having mythical roots and messianic projection from this discovery. Los juicios finales analyzes the impact of this vision on the social sciences, literature, and visual arts. In this bibliographic review, in addition to examining each section and chapter, I identify the centrality of two figures for the book’s objectives and organization: José María Arguedas (who was the most creative disseminator of the new perspective on Andean mentalities) and Alberto Flores Galindo (whose thesis on the “Andean utopia” has substantial differences from that of “Andean messianism”). Finally, this bibliographic review comments on some limitations of Los juicios finales, particularly the absence of an intersectional perspective of gender, race, and class that relativizes the scene (invoked in the introduction) of the “encounter between the intellectual and the Andean man.”